Refinement and preliminary evaluation of two tablet-based tests of real-world visual function - Pete R Jones; Iris Tigchelaar; Giorgia Demaria; Iain Wilson; Wei Bi; Deanna J Taylor; David P Crabb (WILEY, 2022)
Purpose
To describe, refine, evaluate, and provide normative control data for two freely available tablet-based tests of real-world visual function, using a cohort of young, normally-sighted adults.
Methods
Fifty young (18-40 years), normally-sighted adults completed tablet-based assessments of (1) face discrimination and (2) visual search. Each test was performed twice, to assess test-retest repeatability. Post-hoc analyses were performed to determine the number of trials required to obtain stable estimates of performance. Distributions were fitted to the normative data to determine the 99% population-boundary for normally sighted observers. Participants were also asked to rate their comprehension of each test.
Results
Both tests provided stable estimates in around 20 trials (~1-4 min), with only a further reduction of 14%-17% in the 95% Coefficient of Repeatability (CoR95) when an additional 40 trials were included. When using only ~20 trials: median durations for the first run of each test were 191 s (Faces) and 51 s (Search); test-retest CoR95 were 0.27 d (Faces) and 0.84 s (Search); and normative 99% population-limits were 3.50 d (Faces) and 3.1 s (Search). No participants exhibited any difficulties completing either test (100% completion rate), and ratings of task-understanding were high (Faces: 9.6 out of 10; Search: 9.7 out of 10).
Conclusions
This preliminary assessment indicated that both tablet-based tests are able to provide simple, quick, and easy-to-administer measures of real-world visual function in normally-sighted young adults. Further work is required to assess their accuracy and utility in older people and individuals with visual impairment. Potential applications are discussed, including their use in clinic waiting rooms, and as an objective complement to Patient Reported Outcome Measures (PROMs).